The Effect of Sales Growth, Profit Growth, and Firm Size on Stock Prices at PT Indofood (CBP) Sukses Makmur Tbk - Sriwahyuningsih Sriwahyuningsih; Nurul Huda; Julaiha Julaiha (Journal of Economics, Management and Accounting (JEMA), 2025)
This study aims to analyze the influence of sales growth, profit growth, and company size on stock prices at PT Indofood (CBP) Sukses Makmur Tbk. The research is motivated by the importance of financial performance indicators in determining stock price movements, as investors often use these variables to evaluate company value. The study employs a quantitative approach using secondary data from the company’s financial reports and stock market performance. Multiple linear regression is applied to test the effect of the independent variables on the dependent variable. The findings show that sales growth and profit growth have a significant positive effect on stock prices, while company size does not show a significant influence. These results indicate that investors pay more attention to financial performance related to growth factors rather than company size in making investment decisions.